2009
DOI: 10.2486/indhealth.47.503
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence (SOC) may Reduce the Effects of Occupational Stress on Mental Health Status among Japanese Factory Workers

Abstract: To examine if sense of coherence (SOC) can reduce the adverse effects of job stress on mental health status, self-administered questionnaires were distributed among 740 workers in a manufacturing industry. The questionnaire contained SOC, Job Content Questionnaire (JCQ), and General Health Questionnaire (GHQ-12). Complete answers were recovered from 466 workers (62.8%), consisting of 387 males and 79 females, with ages of 45.1 ± 12.0 yr, and used for the analysis. The logistic regression analysis revealed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 24 publications
4
29
1
Order By: Relevance
“…SOC scores should be regarded as complementary to and not a substitute for information already known to be associated with an increased risk for future illness (Suominena et al 2001). Our results demonstrated that SOC scores within the low GHQ-12 group were significantly higher than those in the high GHQ group, which is consistent with previous studies (Matsuzaki et al 2007;Sagara et al 2009;Urakawa and Yokoyama 2009). Generally, the GHQ-12 has been used in primary health care screenings in general population surveys as well as in general medical practice (Doi and Minowa 2003).…”
Section: Discussionsupporting
confidence: 90%
“…SOC scores should be regarded as complementary to and not a substitute for information already known to be associated with an increased risk for future illness (Suominena et al 2001). Our results demonstrated that SOC scores within the low GHQ-12 group were significantly higher than those in the high GHQ group, which is consistent with previous studies (Matsuzaki et al 2007;Sagara et al 2009;Urakawa and Yokoyama 2009). Generally, the GHQ-12 has been used in primary health care screenings in general population surveys as well as in general medical practice (Doi and Minowa 2003).…”
Section: Discussionsupporting
confidence: 90%
“…68,69 For example, research indicates that a person with a strong SOC experiences not only a better quality of life, but also favorable health outcomes. 68,70 The response to each question was a rating between 1 and 7, resulting in SOC scores ranging from 13 to 91. High scores reflect a greater sense of coherence or personal control over one's life.…”
Section: Sense Of Coherence Questionnairementioning
confidence: 99%
“…Therefore, a strong relation found between SOC and stress confirmed the protective role of SOC in our study. According to the scientific data, a strong sense of coherence has a positive effect on coping with work-related stress [31,35,53,55] and occupational problems [30]; employees with a stronger SOC are better protected from the negative effects of some work stressors [56].According to scientific data, employees with a different level of SOC perceive psychosocial environment differently -associations are significant between SOC and high work demands, social support, influence at work [33] as well as low job control [57], adverse organizational climate and job insecurity [58]. A protective role of SOC was observed when the employees experienced negative changes of the psychosocial work environment during an organizational merger [59].…”
Section: Discussionmentioning
confidence: 99%
“…Stronger SOC allows adopting a problemfocused coping profile that allows for better coping with work-related stressors [30]. High SOC enables workers to cope with their job demands -which are a potent job stressor -indicating that SOC is an important factor determining their coping ability [31]. It follows that a good stress management capability allows for avoiding adverse consequences of stress [27].…”
Section: Introductionmentioning
confidence: 99%